Wave-absorbing heat-conducting super-hydrophobic anticorrosive coating and preparation method thereof

By using composite materials of boron nitride nanosheets and carbon nanoparticles and porous hollow SiO2 structures in the coating, combined with polyurethane matrix, the existing coating cannot simultaneously possess wave absorption, thermal conductivity and superhydrophobic properties under complex environmental conditions. The problem of this achieves efficient electromagnetic shielding and thermal management performance.

CN119242146AActive Publication Date: 2025-01-03XIAN UNIV OF TECH

Patent Information

Application Number
CN202411393197.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-03
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

It is difficult for existing coatings to have efficient wave absorption, excellent thermal conductivity and superhydrophobic surface characteristics at the same time, resulting in the inability to fully respond to electromagnetic shielding and thermal management needs under complex and changing environmental conditions.

Method used

By preparing a composite material of boron nitride nanosheets (BNNS) and carbon nanoparticles, a sandwich structure and a porous hollow SiO2 coated structure are constructed, combined with a polyurethane matrix, an efficient conductive network and thermal conduction path are formed, and through SiO2 nanoparticles and porous hollow SiO2 Structure enhances superhydrophobic performance.

Benefits of technology

It realizes a multifunctional composite coating with efficient wave absorption, excellent thermal conductivity and superhydrophobic properties, and can be widely used in electromagnetic shielding, thermal management, waterproofing and anti-fouling, etc., to meet the diversified needs of high performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242146A_ABST
    Figure CN119242146A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following specific steps: firstly, loading carbon nanoparticles and SiO2 nanoparticles on the surface of BNNS to obtain 1-BNNS / C / SiO2, then preparing a porous hollow SiO2 coated BNNS / C composite material (2-BNNS / C / SiO2), and mixing double-structure BNNS / C / SiO2 as a polyurethane filler to obtain the wave-absorbing and heat-conducting super-hydrophobic anticorrosive coating. The coating consists of a polyurethane matrix and two BNNS / C / SiO2 composite materials with different structures, and the structure of the 1-BNNS / C / SiO2 composite material is as follows: carbon nanoparticles are uniformly loaded on the surface of BNNS, and then SiO2 microspheres are uniformly grown on the surface of the BNNS; the structure of the 2-BNNS / C / SiO2 composite material is as follows: BNNS uniformly loaded with carbon nanoparticles is wrapped by porous and mesoporous SiO2 microspheres. According to the prepared wave-absorbing and heat-conducting type super-hydrophobic anticorrosive coating, the tight attachment of the carbon nanoparticles and the SiO2 nanoparticles on the surface of the BNNS is fully utilized, and an efficient conductive network and a heat conduction path are constructed. And the BNNS and the porous SiO2 microspheres can optimize impedance and enhance wave absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal surface coating protection and relates to a method for preparing a wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating. Background Art

[0002] In the field of metal surface coating protection, the rapid progress of science and technology and the continuous expansion of industrial applications have led to increasingly stringent requirements on the functionality and performance of coating materials. These materials not only need to resist environmental erosion, but also need to achieve efficient thermal management, electromagnetic shielding, and excellent waterproof and anti-fouling functions under extreme conditions. For example, in the aerospace field, extreme conditions such as high temperature, high-speed friction, and strong electromagnetic radiation caused by high-speed flight require coating materials to have excellent thermal conductivity to quickly dissipate heat, efficient wave absorption to reduce radar reflection cross section, and super hydrophobicity to prevent the accumulation of water droplets in high-altitude environments, thereby ensuring the safety and stability of aircraft. In the field of electronic communications, as electronic equipment develops towards a higher degree of integration, electromagnetic interference and thermal management have become key factors restricting their performance.

[0003] Although traditional coating fillers can protect metal substrates from environmental factors such as corrosion and wear to a certain extent, their limitations are gradually revealed in the face of increasingly complex and diversified demands in modern industry. For example, thermal conductive materials such as graphene and carbon nanotubes are widely used in coating fillers due to their excellent thermal conductivity, which greatly improves the thermal management efficiency of the coating. However, when these materials are used alone, their wave absorption performance is difficult to meet high-performance requirements, limiting their application in key areas such as electromagnetic shielding. At the same time, superhydrophobic materials such as fluorinated polymers and nanostructured surfaces effectively reduce the adhesion of moisture and pollutants through their unique surface properties, but often sacrifice other key properties. Therefore, the development of a multifunctional coating that can simultaneously take into account thermal conductivity, wave absorption and superhydrophobic properties has become a hot topic in current research.

[0004] The Chinese patent "A high-temperature resistant absorbing coating with a low thermal expansion coefficient and a preparation method thereof" (application number: CN202311453978.9, publication number: CN117363068A, announcement date: 2024.01.09) provides a high-temperature resistant absorbing coating with a low thermal expansion coefficient and a preparation method thereof. The high-temperature resistant absorbing coating in the application has a low thermal expansion coefficient and can achieve good geothermal matching with a substrate formed of a low expansion coefficient material, and can still effectively absorb electromagnetic waves after annealing in a high-temperature environment, thereby improving the target's absorbing performance and service life in a high-temperature environment, but its functionality or adaptability is relatively single, and it is difficult to fully cope with complex and changeable environmental conditions.

[0005] The Chinese patent "A self-cleaning, waterproof and anti-corrosion powder coating and its preparation method" (application number: CN202410853650.4, publication number: CN118440569A, announcement date: 2024.08.06) provides a self-cleaning, waterproof and anti-corrosion powder coating and its preparation method. The coating is composed of modified polyester-epoxy powder coating, nano-active powder and dispersant. Although it has excellent corrosion resistance, high hardness, wear resistance, waterproof and self-cleaning properties, its performance coverage is not comprehensive, which limits its application in a wider range of fields.

[0006] The Chinese patent "A homogeneous flexible super-hydrophobic absorbing coating and its preparation method and application" (application number: CN202310835078.4, publication number: CN116855120A, announcement date: 2023.10.10) discloses a homogeneous flexible super-hydrophobic absorbing coating and its preparation method and application. The absorbing material is modified by organic-inorganic hybridization, and the sulfur free radicals are grafted to the surface of the absorber by reverse sulfidation reaction. At the same time, the monomer wraps it, which can reduce the dielectric property of the material and improve the impedance mismatch. A coating with certain super-hydrophobicity and good absorbing performance is obtained. However, materials with high electromagnetic loss are often accompanied by higher thermal conductivity. Excessive thermal conductivity may be unfavorable for the local accumulation and control of heat, limiting its application field.

[0007] The Chinese patent "A high thermal conductivity coated aluminum foil and its preparation process" (application number: CN202410794297.7, publication number: CN118359981A, announcement date: 2015.11.18) discloses a high thermal conductivity coated aluminum foil and its preparation process, using polyethylene glycol as the core material, then adding benzotriazole as an anticorrosive agent, and then using lead tungstate with excellent thermal conductivity as the shell to prepare a thermally conductive and corrosion-resistant microcapsule, and then coating the surface of the microcapsule with a layer of silicon dioxide to further improve the anticorrosion performance of the microcapsule. However, there are also problems such as insufficient performance and limited application areas. Summary of the invention

[0008] The present invention has two purposes. The first purpose is to provide a method for preparing a wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating, which solves the problem that existing coatings are difficult to meet the diversified and high-performance requirements of high-efficiency wave absorption, excellent thermal conductivity and super-hydrophobic surface characteristics. The second purpose of the present invention is to provide a wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating to solve the problem that the existing coatings have poor electromagnetic shielding effect and weak thermal conductivity.

[0009] The present invention provides a method for preparing a wave absorbing heat conducting super hydrophobic anti-corrosion coating, which is specifically implemented according to the following steps:

[0010] Step 1, preparation of boron nitride nanosheets (BNNS)

[0011] The boron nitride particles were mixed with isopropanol and ball-milled, and then ultrasonicated for 30 min using an ultrasonic cell crusher, and then centrifuged and filtered, and washed three times with deionized water and ethanol respectively, and freeze-dried for 6 h to obtain boron nitride nanosheets (BNNS).

[0012] Step 2: Loading carbon nanoparticles

[0013] The BNNS obtained in step 1 and the water-soluble polymer are added to deionized water, heated in a water bath and stirred, and then dried and calcined in a nitrogen atmosphere to obtain a BNNS / C composite material.

[0014] Step 3: Construction of sandwich structure BNNS / C / SiO2 composite material

[0015] The BNNS / C composite material obtained in step 2 is ultrasonically dispersed in a mixed solution of anhydrous ethanol and deionized water, and then N, N, N', N'-tetramethyl-1, 4-butanediamine (TMBDM), tetraethyl orthosilicate (TEOS), and hexamethyldisilazane (HMDS) are added in sequence, stirred at room temperature for reaction, centrifuged and washed three times with ethanol and deionized water, and finally dried to obtain a sandwich structure 1-BNNS / C / SiO2 composite material.

[0016] Step 4: Preparation of porous hollow SiO2-coated BNNS / C composites

[0017] The BNNS / C obtained in step 2 is ultrasonically dispersed in a mixed solution of anhydrous ethanol and deionized water, and then cetyltrimethylammonium bromide (CTAB) and ammonia water are added and stirred evenly; resorcinol is added under continuous stirring for reaction for 30 minutes, and then TEOS and formaldehyde are added dropwise, and the reaction is stirred at room temperature; the reaction product is centrifuged, washed with anhydrous ethanol and deionized water, dried, and calcined in a muffle furnace to obtain a porous hollow SiO2-coated BNNS / C composite material (2-BNNS / C / SiO2).

[0018] Step 5: Preparation of a wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating

[0019] The 1-BNNS / C / SiO2 composite material obtained in step 3 and the 2-BNNS / C / SiO2 composite material obtained in step 4 are mixed with polyurethane in a certain mass ratio, mixed evenly by a blender and then ultrasonically dispersed, and the above stirring and ultrasonic dispersion are repeated multiple times; a curing agent is added, stirred evenly and then applied on an aluminum plate, and after complete curing, a wave-absorbing and heat-conductive super-hydrophobic anti-corrosion coating is obtained.

[0020] The invention discloses a wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating, which is composed of a polyurethane matrix and two BNNS / C / SiO2 composite materials with different structures, wherein the structure of the 1-BNNS / C / SiO2 composite material is that carbon nanoparticles are uniformly loaded on the surface of BNNS, and then SiO2 microspheres are uniformly grown on the surface; and the structure of the 2-BNNS / C / SiO2 composite material is that BNNS uniformly loaded with carbon nanoparticles is wrapped in porous mesoporous SiO2 microspheres.

[0021] The present invention is also characterized in that:

[0022] In step 1, the ball-to-material ratio is 80:1-100:1, the agent-to-material ratio is 50:1-60:1, the rotation speed is 400r / min-500r / min, the ball milling time is 8h-12h; the centrifugal speed is 2000rpm-3000rpm, and the time is 15min-30min.

[0023] The mass ratio of BNNS to water-soluble polymer in step 2 is 1:5-1:10, the mass ratio of water-soluble polymer to deionized water is 1:30-1:50, the water-soluble polymer is any one of polyvinyl alcohol, sucrose, glucose, chitosan, etc., the stirring temperature is 80°C-90°C, the stirring time is 1h-2h, the drying temperature is 80°C, the drying time is 8h-12h, and the calcination parameters are: the heating rate is 3°C / min, the calcination temperature is 800°C-1000°C, and the insulation time is 2h-4h.

[0024] The concentration of BNNS / C in the mixed solution of anhydrous ethanol and deionized water in step 3 is 0.01 g / mL to 0.02 g / mL, the volume ratio of anhydrous ethanol to deionized water is 3:1 to 6:1, the volume ratios of TMBDM, HMDS, TEOS to deionized water are 1:80 to 1:20, 1:10 to 1:30, and 1:1 to 1:3, respectively, the reaction time is 4 h to 8 h, the centrifugal speed is 2000 rpm to 3000 rpm, the centrifugal time is 15 min to 30 min, the drying temperature is 60°C to 80°C, and the drying time is 6 h to 12 h.

[0025] The concentration of BNNS / C in the mixed solution of anhydrous ethanol and deionized water in step 4 is 0.01 g / mL to 0.02 g / mL, the volume ratio of anhydrous ethanol to deionized water is 1:2 to 1:4, the mass ratio of BNNS / C to CTAB is 1:3 to 1:5, the volume ratio of ammonia water to anhydrous ethanol is 1:60 to 1:80, the mass ratio of resorcinol to CTAB is 1:2 to 2:1, the volume ratio of TEOS to anhydrous ethanol is 1:5 to 1:10, the volume ratio of formaldehyde to anhydrous ethanol is 1:10 to 1:20, the reaction time is 4 h to 6 h, the centrifugal speed is 2000 rpm to 3000 rpm, the time is 15 min to 30 min, the drying temperature is 60 ° C to 80 ° C, the drying time is 6 h to 12 h, and the parameters of calcination in the muffle furnace are: the heating rate is 5 ° C / min, the temperature is 550 ° C, and the holding time is 4 h to 6 h.

[0026] The mass ratio of the 1-BNNS / C / SiO2 composite material to the 2-BNNS / C / SiO2 composite material in step 5 is 1:5 to 1:1, the filling rate of the total mass of the two composite materials in the polyurethane is 10% to 60%, the stirrer speed is 500rpm to 800rpm, the stirring time is 20min to 60min, the ultrasonic time is 15min to 30min, the number of repetitions is 2 to 4 times, the curing agent is one of the trimers of toluene diisocyanate (TDI), 1,6-hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI), the mass ratio of the curing agent to the total mass of the 1-BNNS / C / SiO2 composite material and the 2-BNNS / C / SiO2 composite material is 1:500 to 1:1000, and the stirring time is 1min to 3min.

[0027] The beneficial effects of the present invention are: a method for preparing a wave-absorbing heat-conducting super-hydrophobic anti-corrosion coating, which can obtain a multifunctional composite coating integrating efficient wave absorption, excellent thermal conductivity and super-hydrophobic performance. Carbon nanoparticles are closely attached to the surface of BNNS, construct an efficient conductive network, accelerate electron migration and polarization, and BNNS is used as an impedance matching layer to optimize electromagnetic absorption. By introducing porous SiO2 microspheres, not only the specific surface area is increased, but also the effective scattering and absorption of electromagnetic waves are achieved by using its unique pores. Further, BNNS with excellent thermal conductivity is combined with carbon nanoparticles and SiO2 nanoparticles to construct an efficient heat conduction path, while SiO2 nanoparticles and porous hollow SiO2 structures form a rough micro-nano structure on the coating surface, increase the thickness of the air layer on the coating surface, and enhance super-hydrophobic performance. Therefore, the coating is expected to be widely used in multiple fields such as electromagnetic shielding, thermal management, waterproofing and antifouling, and has important practical value and far-reaching economic and social significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the microscopic morphology of the 1-BNNS / C / SiO2 composite filler prepared by the present invention.

[0029] Figure 2 It is a schematic diagram of the microscopic morphology of the 2-BNNS / C / SiO2 composite filler prepared by the present invention.

[0030] In the figure, 1-BNNS, 2-carbon nanoparticles, 3-SiO2 nanoparticles, 4-porous SiO2 microspheres DETAILED DESCRIPTION

[0031] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] The technical solution adopted by the present invention is a method for preparing a wave-absorbing heat-conducting super-hydrophobic anti-corrosion coating, which is specifically implemented according to the following steps:

[0033] Step 1, Boron Nitride Nanosheets (BNNS):

[0034] The boron nitride particles were mixed with isopropanol for ball milling, wherein the ball-to-material ratio was 80:1-100:1, the agent-to-material ratio was 50:1-60:1, the rotation speed was 400r / min-500r / min, and the ball milling time was 8h-12h. Then, an ultrasonic cell crusher was used for ultrasonication for 30min, centrifuged at a speed of 2000rpm-3000rpm for 15min-30min and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and freeze-dried for 6h to obtain BNNS.

[0035] Step 2, loading carbon nanoparticles;

[0036] The BNNS obtained in step 1 and a water-soluble polymer are added to deionized water in a mass ratio of 1:5 to 1:10, wherein the mass ratio of the water-soluble polymer to deionized water is 1:30 to 1:50, and the water-soluble polymer is any one of polyvinyl alcohol, sucrose, glucose, chitosan, etc., heated in a water bath at 80°C to 90°C with stirring for 1h to 2h, dried at 80°C for 8h to 12h, and then calcined at 800°C to 1000°C at 3°C / min in a nitrogen atmosphere, and kept warm for 2h to 4h to obtain a BNNS / C composite material.

[0037] Step 3: Construct sandwich structure BNNS / C / SiO2 composite material:

[0038] The BNNS / C composite material obtained in step 2 is ultrasonically dispersed in a mixed solution of anhydrous ethanol and deionized water at a concentration of 0.01 g / mL to 0.02 g / mL, wherein the volume ratio of anhydrous ethanol to deionized water is 3:1 to 6:1, and then N, N, N', N'-tetramethyl-1,4-butanediamine (TMBDM), tetraethyl orthosilicate (TEOS), and hexamethyldisilazane (HMDS) are added in sequence, and the volume ratios of TMBDM, HMDS, TEOS and deionized water are 1:80 to 1:20, 1:10 to 1:30, and 1:1 to 1:3, respectively. The reaction is stirred at room temperature for 4h to 8h, centrifuged at a speed of 2000rpm to 3000rpm for 15min to 30min, separated, washed three times with ethanol and deionized water, and dried at 60℃ to 80℃ for 6h to 12h to obtain a sandwich structure 1-BNNS / C / SiO2 composite material.

[0039] Step 4, preparation of porous hollow SiO2 coated BNNS / C composite material:

[0040] The BNNS / C obtained in step 2 is ultrasonically dispersed in a mixed solution of anhydrous ethanol and deionized water, wherein the concentration of BNNS / C in the mixed solution of anhydrous ethanol and deionized water is 0.01 g / mL to 0.02 g / mL, and the volume ratio of anhydrous ethanol to deionized water is 1:2 to 1:4. Subsequently, hexadecyltrimethylammonium bromide (CTAB) and ammonia water are added and stirred evenly, the mass ratio of BNNS / C to CTAB is 1:3 to 1:5, and the volume ratio of ammonia water to anhydrous ethanol is 1:60 to 1:80. Resorcinol is added under continuous stirring for reaction for 30 minutes, and then TEOS and formaldehyde are added dropwise. The mass ratio of resorcinol to CTAB is 1:3 to 1:5. The ratio is 1:2 to 2:1, the volume ratio of TEOS to anhydrous ethanol is 1:5 to 1:10, and the volume ratio of formaldehyde to anhydrous ethanol is 1:10 to 1:20, and the reaction is stirred at room temperature for 4h to 6h; the reaction product is centrifuged at a speed of 2000rpm to 3000rpm for 15min to 30min, washed with anhydrous ethanol and deionized water, dried at 60℃ to 80℃ for 6h to 12h, and calcined in a muffle furnace at a heating rate of 5℃ / min, the temperature is 550℃, and the insulation time is 4h to 6h to obtain a porous hollow SiO2-coated BNNS / C composite material (2-BNNS / C / SiO2).

[0041] Step 5: Preparation of a wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating

[0042] The 1-BNNS / C / SiO2 composite material obtained in step 3 and the 2-BNNS / C / SiO2 composite material obtained in step 4 are mixed with polyurethane in a mass ratio of 1:5 to 1:1, and the filling rate of the total mass of the two composite materials in the polyurethane is 10% to 60%. The mixture is stirred for 20 min to 60 min at a rotation speed of 500 rpm to 800 rpm by a stirrer, and then ultrasonically dispersed for 15 min to 30 min, and the above stirring and ultrasonic dispersion are repeated 2 to 4 times; a curing agent is added, wherein the curing agent is one of the trimers of toluene diisocyanate (TDI), 1,6-hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI), and the mass ratio of the curing agent to the total mass of the 1-BNNS / C / SiO2 composite material and the 2-BNNS / C / SiO2 composite material is 1:500 to 1:1000. After stirring for 1 min to 3 min, it is applied to an aluminum plate, and after complete curing, a wave-absorbing and heat-conductive super-hydrophobic anti-corrosion coating is obtained.

[0043] The present invention uses fine ball milling technology to peel off boron nitride to prepare BNNS with high specific surface area, providing a basis for subsequent functionalization; water-soluble polymer precursors are used to prepare carbon nanoparticles, and they are tightly attached to the surface of BNNS with SiO2 nanoparticles to construct an efficient conductive and thermal conduction network, enhance wave absorption and surface roughness, and use CTAB as a template to control the proportion of each raw material to form a structure of hollow porous SiO2 microspheres coated with BNNS / C, thereby increasing the specific surface area of ​​the material, and optimizing the impedance matching of the material through its unique pores, thereby achieving effective scattering and absorption of electromagnetic waves; the mixed dual-structure BNNS / C / SiO2 is used as a polyurethane filler to optimize the filling rate and construct a multi-level composite structure, which significantly improves the wave absorption, thermal conductivity and super-hydrophobicity properties to meet the needs of high-performance diversification.

[0044] The present invention discloses a wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating. Carbon nanoparticles are tightly attached to the surface of BNNS to build an efficient conductive network, accelerate electron migration and polarization, and BNNS serves as an impedance matching layer to optimize electromagnetic absorption. By introducing porous SiO2 microspheres, not only the specific surface area is increased, but also the effective scattering and absorption of electromagnetic waves are achieved by utilizing its unique pores. Furthermore, BNNS with excellent thermal conductivity is combined with carbon nanoparticles and SiO2 nanoparticles to construct an efficient heat conduction path. At the same time, SiO2 nanoparticles and porous hollow SiO2 structures form a rough micro-nano structure on the coating surface, increase the thickness of the air layer on the coating surface, and enhance super-hydrophobic performance. Therefore, the coating is expected to be widely used in multiple fields such as electromagnetic shielding, thermal management, waterproofing and antifouling, and has important practical value.

[0045] Example 1 Preparation of wave-absorbing heat-conducting super-hydrophobic anti-corrosion coating 1

[0046] First, 3 g of boron nitride particles, 150 g of isopropanol and 240 g of ball milling beads were weighed and put into a ball mill, and ball milled at 400 rpm for 8 h. Then, ultrasonic cell crusher was used for 30 min, and centrifuged at 2000 rpm for 15 min. The supernatant was vacuum filtered, washed three times with deionized water and anhydrous ethanol respectively, and freeze-dried for 6 h to obtain BNNS.

[0047] Weigh 0.5 g BNNS and 2.5 g polyvinyl alcohol, add into 125 mL deionized water, heat in a water bath at 80 °C and stir for 1 h; then dry at 80 °C for 8 h to obtain BNNS / C precursor; calcine at a heating rate of 3 °C / min in a nitrogen atmosphere, the calcination temperature is 800 °C, and keep warm for 2 h to obtain BNNS / C composite material.

[0048] 0.7 g of BNNS / C composite material was weighed and ultrasonically dispersed in a mixed solution of 60 mL of anhydrous ethanol and 10 mL of deionized water, followed by adding 0.125 mL of TMBDM, 0.333 mL of HMDS and 3.3 mL of LTEOS, stirring at room temperature and reacting for 4 hours; the obtained solution was then centrifuged at 2000 rpm for 15 minutes, and the precipitate was separated and washed three times with anhydrous ethanol and deionized water, and dried at 60°C for 6 hours to obtain a sandwich structure 1-BNNS / C / SiO2 composite material.

[0049] 0.5 g BNNS / C composite material was weighed and ultrasonically dispersed in a mixed solution of 10 mL anhydrous ethanol and 40 mL deionized water, and then 1.5 g CTAB and 0.125 mL ammonia water were added. After stirring evenly, 0.75 g resorcinol was added under continuous stirring for 30 min, and then 1 mL LTEOS and 0.5 mL formaldehyde were added. The reaction was stirred continuously at room temperature for 4 h. The reaction product was centrifuged at 2000 rpm for 15 min, washed with anhydrous ethanol and deionized water, dried at 60 °C for 6 h, and calcined in a muffle furnace at a heating rate of 5 °C / min, a temperature of 550 °C, and a holding time of 4 h to obtain a porous hollow SiO2-coated BNNS / C composite material (2-BNNS / C / SiO2).

[0050] Weigh 0.33g1-BNNS / C / SiO2 and 1.67g2-BNNS / C / SiO2 and mix them with 20g polyurethane, stir them in a blender at a speed of 500rpm for 20min, and then ultrasonically disperse them for 15min, and repeat the above stirring and ultrasonic steps twice; add 0.002gTDI, stir for 1min, and then evenly apply it on an aluminum plate, and after complete curing, a wave-absorbing and heat-conductive super-hydrophobic anti-corrosion coating is obtained.

[0051] Example 2 Preparation of BNNS / C / SiO2 / Fe3O4 composite filler 2

[0052] First, 3 g of boron nitride particles, 180 g of isopropanol and 300 g of ball milling beads were weighed and put into a ball mill, and ball milled at 500 rpm for 12 h. Then, ultrasonic cell crusher was used for 30 min, and centrifuged at 3000 rpm for 30 min. The supernatant was vacuum filtered, washed three times with deionized water and anhydrous ethanol respectively, and freeze-dried for 6 h to obtain BNNS.

[0053] Weigh 0.5 g BNNS and 5 g sucrose, add into 150 mL deionized water, heat in a water bath at 90 °C and stir for 2 h; then dry at 80 °C for 12 h to obtain BNNS / C precursor; calcine at a heating rate of 3 °C / min in a nitrogen atmosphere, the calcination temperature is 1000 °C, and keep warm for 4 h to obtain BNNS / C composite material.

[0054] 0.8 g of BNNS / C composite material was weighed and ultrasonically dispersed in a mixed solution of 30 mL of anhydrous ethanol and 10 mL of deionized water, followed by adding 0.5 mL of TMBDM, 1 mL of HMDS and 10 mL of LTEOS, stirring at room temperature and reacting for 8 h; the resulting solution was centrifuged at 3000 rpm for 30 min, and the precipitate was separated and washed three times with anhydrous ethanol and deionized water, and dried at 80 °C for 12 h to obtain a sandwich structure 1-BNNS / C / SiO2 composite material.

[0055] 0.6 g BNNS / C composite material was weighed and ultrasonically dispersed in a mixed solution of 10 mL anhydrous ethanol and 20 mL deionized water, and then 3 g CTAB and 0.167 mL ammonia water were added. After stirring evenly, 6 g resorcinol was added under continuous stirring for 30 min, and then 2 ml LTEOS and 1 mL formaldehyde were added. The reaction was stirred continuously at room temperature for 6 h. The reaction product was centrifuged at 3000 rpm for 30 min, washed with anhydrous ethanol and deionized water, dried at 80 °C for 12 h, and calcined in a muffle furnace at a heating rate of 5 °C / min, a temperature of 550 °C, and a holding time of 6 h to obtain a porous hollow SiO2-coated BNNS / C composite material (2-BNNS / C / SiO2).

[0056] Weigh 2g1-BNNS / C / SiO2 and 3g2-BNNS / C / SiO2 and mix them with 20g polyurethane, stir them in a blender at a speed of 800rpm for 60min, and then ultrasonically disperse them for 30min. Repeat the above stirring and ultrasonic steps 4 times; add 0.024gHDI, stir for 3min, and then evenly apply it on an aluminum plate. After complete curing, a wave-absorbing and heat-conductive super-hydrophobic anti-corrosion coating is obtained.

[0057] Example 3 Preparation of BNNS / C / SiO2 / Fe3O4 composite filler 3

[0058] First, 3 g of boron nitride particles, 160 g of isopropanol and 260 g of ball milling beads were weighed and put into a ball mill, and the mixture was ball milled at 450 rpm for 10 h. Then, an ultrasonic cell crusher was used for ultrasonication for 30 min, and the mixture was centrifuged at 2500 rpm for 20 min. The supernatant was vacuum filtered, washed three times with deionized water and anhydrous ethanol respectively, and freeze-dried for 6 h to obtain BNNS.

[0059] Weigh 0.5 g BNNS and 3 g glucose, add into 120 mL deionized water, heat in a water bath at 85 °C and stir for 1.5 h; then dry at 85 °C for 10 h to obtain BNNS / C precursor; calcine at a heating rate of 3 °C / min in a nitrogen atmosphere, the calcination temperature is 900 °C, and keep warm for 3 h to obtain BNNS / C composite material.

[0060] 0.5 g of BNNS / C composite material was weighed and ultrasonically dispersed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, followed by adding 0.3 mL of TMBDM, 0.5 mL of HMDS and 5 mL of LTEOS, stirring at room temperature and reacting for 6 h; the resulting solution was centrifuged at 2500 rpm for 20 min, and the precipitate was separated and washed three times with anhydrous ethanol and deionized water, and dried at 70 °C for 10 h to obtain a sandwich structure 1-BNNS / C / SiO2 composite material.

[0061] 0.4 g BNNS / C composite material was weighed and ultrasonically dispersed in a mixed solution of 10 mL anhydrous ethanol and 30 mL deionized water, and then 1.6 g CTAB and 0.15 mL ammonia water were added. After stirring evenly, 1.6 g resorcinol was added under continuous stirring for 30 min, and then 1.5 mL LTEOS and 0.7 mL formaldehyde were added. The reaction was stirred continuously at room temperature for 5 h; the reaction product was centrifuged at a speed of 2500 rpm for 20 min, washed with anhydrous ethanol and deionized water, dried at 70 ° C for 10 h, and calcined in a muffle furnace at a heating rate of 5 ° C / min, the temperature was 550 ° C, and the insulation time was 5 h to obtain a porous hollow SiO2-coated BNNS / C composite material (2-BNNS / C / SiO2).

[0062] Weigh 3g1-BNNS / C / SiO2 and 3g2-BNNS / C / SiO2 and mix them with 20g polyurethane, stir them in a blender at 600rpm for 40min, and then ultrasonically disperse them for 20min, and repeat the above stirring and ultrasonic steps 3 times; add 0.008gIPDI trimer, stir for 2min, and evenly apply it on an aluminum plate, and after complete curing, a wave-absorbing and heat-conductive super-hydrophobic anti-corrosion coating is obtained.

[0063] Example 4 Preparation of BNNS / C / SiO2 / Fe3O4 composite filler 4

[0064] First, 3 g of boron nitride particles, 170 g of isopropanol and 270 g of ball milling beads were weighed and put into a ball mill, and ball milled at 400 rpm for 10 h. Then, ultrasonic cell crusher was used for 30 min, and centrifuged at 2500 rpm for 25 min. The supernatant was vacuum filtered, washed three times with deionized water and anhydrous ethanol respectively, and freeze-dried for 6 h to obtain BNNS.

[0065] Weigh 0.5 g BNNS and 4 g chitosan, add into 150 mL deionized water, heat in a water bath at 80 °C and stir for 2 h; then dry at 80 °C for 10 h to obtain BNNS / C precursor; calcine at a heating rate of 3 °C / min in a nitrogen atmosphere, the calcination temperature is 950 °C, and keep warm for 3 h to obtain BNNS / C composite material.

[0066] 0.75 g of BNNS / C composite material was weighed and ultrasonically dispersed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, followed by adding 0.25 mL of TMBDM, 0.8 mL of HMDS and 8 mL of LTEOS, stirring at room temperature and reacting for 5 h; the resulting solution was centrifuged at 3000 rpm for 30 min, and the precipitate was separated and washed three times with anhydrous ethanol and deionized water, and dried at 80 °C for 10 h to obtain a sandwich structure 1-BNNS / C / SiO2 composite material.

[0067] 0.75g BNNS / C composite material was weighed and ultrasonically dispersed in a mixed solution of 10mL anhydrous ethanol and 40mL deionized water, and then 3g CTAB and 0.14mL ammonia water were added. After stirring evenly, 5g resorcinol was added under continuous stirring for 30min, and then 1.5mLTEOS and 0.8mL formaldehyde were added. The reaction was stirred continuously at room temperature for 5h. The reaction product was centrifuged at 3000rpm for 30min, washed with anhydrous ethanol and deionized water, dried at 70℃ for 12h, and calcined in a muffle furnace at a heating rate of 5℃ / min, the temperature was 550℃, and the insulation time was 6h to obtain a porous hollow SiO2-coated BNNS / C composite material (2-BNNS / C / SiO2).

[0068] Weigh 4g1-BNNS / C / SiO2 and 6g2-BNNS / C / SiO2 and mix them with 20g polyurethane, stir them in a blender at 600rpm for 50min, and then ultrasonically disperse them for 20min. Repeat the above stirring and ultrasonic steps 4 times; add 0.003gHDI, stir for 3min, and evenly apply it on an aluminum plate. After complete curing, a wave-absorbing and heat-conductive super-hydrophobic anti-corrosion coating is obtained.

[0069] Comparative Example 1

[0070] The only difference from Example 3 is that in step 5, no 1-BNNS / C / SiO2 composite material is added.

[0071] Comparative Example 2

[0072] The only difference from Example 3 is that in step 5, no 2-BNNS / C / SiO2 composite material is added.

[0073] Comparative Example 3

[0074] The only difference from Example 3 is that no carbon nanoparticles are loaded, and BNNS is directly used for the subsequent steps.

[0075] Table 1 is a comparison of the wave absorption, thermal conductivity and super hydrophobic properties of the wave absorbing and heat conducting super hydrophobic anticorrosion coating in Example 3, the coating in Comparative Example 1, the coating in Comparative Example 2 and the coating in Comparative Example 3. As can be seen from Table 1, the wave absorbing and heat conducting super hydrophobic anticorrosion coating in Example 3 has the best comprehensive performance. The coating in Comparative Example 1 lacks 1-BNNS / C / SiO2 composite material, which seriously affects the rough surface micro-nano structure constructed. The lack of 1-BNNS / C / SiO2 composite material in Comparative Example 2 and the lack of porous SiO2 microspheres extend the electromagnetic wave propagation path, thus significantly affecting the wave absorption performance of the material. Due to the lack of carbon nanoparticles in the coating in Comparative Example 3, the effective channel for heat transmission is reduced, the dissipation capacity of electromagnetic waves is weakened, and its thermal conductivity and wave absorption performance are significantly reduced. In the wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating in Example 3, carbon nanoparticles and BNNS can construct an efficient conductive network and heat conduction path, the loading of nano-SiO2 increases the roughness of the material, and the porous SiO2 microspheres promote the scattering and absorption of electromagnetic waves. At the same time, the composite material also has a complex micro-nano structure, which significantly improves the super-hydrophobic performance, so it has the best overall performance and is better than all comparative examples.

[0076] Table 1 compares the wave absorption, thermal conductivity and super hydrophobic properties of the wave absorbing and thermal conductive super hydrophobic anti-corrosion coating in Example 3, the coating in Comparative Example 1, the coating in Comparative Example 2 and the coating in Comparative Example 3.

[0077]

[0078] Figure 1 1-BNNS / C / SiO2 prepared by the present invention is a schematic diagram of the microscopic morphology. Figure 1 It can be seen that carbon nanoparticles and SiO2 nanoparticles are uniformly loaded on the surface of BNNS. Figure 2 Schematic diagram of the microscopic morphology of 2-BNNS / C / SiO2 prepared by the present invention. Figure 2 It can be seen that the hollow porous SiO2 microspheres encapsulate the BNNS uniformly loaded with carbon nanoparticles.

[0079] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a wave-absorbing heat-conducting super-hydrophobic anti-corrosion coating, characterized in that: Please follow the steps below to implement: Step 1, Boron Nitride Nanosheets (BNNS) The boron nitride particles were mixed with isopropanol and ball-milled, and then ultrasonicated for 30 min using an ultrasonic cell crusher, and then centrifuged and filtered, and washed three times with deionized water and ethanol respectively, and freeze-dried for 6 h to obtain BNNS; Step 2: Loading carbon nanoparticles The BNNS and water-soluble polymer obtained in step 1 are added to deionized water, heated in a water bath, and stirred, and then dried and calcined in a nitrogen atmosphere to obtain a BNNS / C composite material; Step 3: Construction of sandwich structure BNNS / C / SiO2 composite material The BNNS / C composite material obtained in step 2 is ultrasonically dispersed in a mixed solution of anhydrous ethanol and deionized water, and then N, N, N', N'-tetramethyl-1, 4-butanediamine (TMBDM), tetraethyl orthosilicate (TEOS), and hexamethyldisilazane (HMDS) are added in sequence, stirred at room temperature for reaction, centrifuged, washed three times with ethanol and deionized water, and finally dried to obtain a sandwich structure 1-BNNS / C / SiO2 composite material; Step 4: Preparation of porous hollow SiO2-coated BNNS / C composites The BNNS / C obtained in step 2 is ultrasonically dispersed in a mixed solution of anhydrous ethanol and deionized water, and then cetyltrimethylammonium bromide (CTAB) and ammonia water are added and stirred evenly; resorcinol is added under continuous stirring for reaction for 30 minutes, and then TEOS and formaldehyde are added dropwise, and the reaction is stirred at room temperature; the reaction product is centrifuged, washed with anhydrous ethanol and deionized water, dried, and calcined in a muffle furnace to obtain a porous hollow SiO2-coated BNNS / C composite material (2-BNNS / C / SiO2); Step 5: Preparation of wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating The 1-BNNS / C / SiO2 composite material obtained in step 3 and the 2-BNNS / C / SiO2 composite material obtained in step 4 are mixed with polyurethane in a certain mass ratio, mixed evenly by a blender and then ultrasonically dispersed, and the above stirring and ultrasonic dispersion are repeated multiple times; a curing agent is added, stirred evenly and then applied on an aluminum plate, and after complete curing, a wave-absorbing and heat-conductive super-hydrophobic anti-corrosion coating is obtained.

2. The method for preparing a wave absorbing heat conducting super hydrophobic anticorrosive coating according to claim 1, characterized in that: In the step 1, the ball-to-material ratio is 80:1-100:1, the agent-to-material ratio is 50:1-60:1, the rotation speed is 400r / min-500r / min, the ball milling time is 8h-12h; the centrifugal speed is 2000rpm-3000rpm, and the time is 15min-30min.

3. The method for preparing a wave absorbing heat conducting super hydrophobic anticorrosive coating according to claim 1, characterized in that: In the step 2, the mass ratio of BNNS to the water-soluble polymer is 1:5-1:10, the mass ratio of the water-soluble polymer to deionized water is 1:30-1:50, the stirring temperature is 80° C.-90° C., and the stirring time is 1 h-2 h.

4. The method for preparing a wave absorbing heat conducting super hydrophobic anticorrosive coating according to claim 1, characterized in that: The water-soluble polymer is any one of polyvinyl alcohol, sucrose, glucose, chitosan and the like.

5. The method for preparing a wave absorbing heat conducting super hydrophobic anticorrosive coating according to claim 1, characterized in that: In the step 3, the concentration of BNNS / C in the mixed solution of anhydrous ethanol and deionized water is 0.01 g / mL to 0.02 g / mL, the volume ratio of anhydrous ethanol to deionized water is 3:1 to 6:1, and the volume ratios of TMBDM, HMDS, TEOS and deionized water are 1:80 to 1:20, 1:10 to 1:30, and 1:1 to 1:3, respectively.

6. The method for preparing a wave-absorbing heat-conducting super-hydrophobic anti-corrosion coating according to claim 1, characterized in that: In the step 3, the reaction time is 4 hours to 8 hours, the centrifugal speed is 2000 rpm to 3000 rpm, the centrifugal time is 15 minutes to 30 minutes, the drying temperature is 60° C. to 80° C., and the drying time is 6 hours to 12 hours.

7. The method for preparing a wave-absorbing heat-conducting super-hydrophobic anti-corrosion coating according to claim 1, characterized in that: In the step 4, the concentration of BNNS / C in the mixed solution of anhydrous ethanol and deionized water is 0.01 g / mL to 0.02 g / mL, the volume ratio of anhydrous ethanol to deionized water is 1:2 to 1:4, the mass ratio of BNNS / C to CTAB is 1:3 to 1:5, the volume ratio of ammonia water to anhydrous ethanol is 1:60 to 1:80, the mass ratio of resorcinol to CTAB is 1:2 to 2:1, the volume ratio of TEOS to anhydrous ethanol is 1:5 to 1:10, and the volume ratio of formaldehyde to anhydrous ethanol is 1:10 to 1:

20.

8. The method for preparing a wave-absorbing heat-conducting super-hydrophobic anti-corrosion coating according to claim 1, characterized in that: In step 4, the reaction time is 4 hours to 6 hours, the centrifugal speed is 2000 rpm to 3000 rpm, the time is 15 minutes to 30 minutes, the drying temperature is 60° C. to 80° C., and the drying time is 6 hours to 12 hours.

9. The method for preparing a wave absorbing heat conducting super hydrophobic anti-corrosion coating according to claim 1, characterized in that: In the step 5, the mass ratio of the 1-BNNS / C / SiO2 composite material to the 2-BNNS / C / SiO2 composite material is 1:5 to 1:1, the filling rate of the total mass of the two composite materials in the polyurethane is 10% to 60%, the stirrer speed is 500rpm to 800rpm, the stirring time is 20min to 60min, the ultrasonic time is 15min to 30min, and the number of repetitions is 2 to 4 times.

10. A wave-absorbing and heat-conducting super-hydrophobic anti-corrosion coating, characterized in that: The coating is composed of a polyurethane matrix and two BNNS / C / SiO2 composite materials with different structures. The structure of the 1-BNNS / C / SiO2 composite material is: carbon nanoparticles are uniformly loaded on the surface of BNNS, and then SiO2 microspheres are uniformly grown on its surface; the structure of the 2-BNNS / C / SiO2 composite material is: porous mesoporous SiO2 microspheres wrap the BNNS uniformly loaded with carbon nanoparticles.

Citation Information

Patent Citations

  • Preparation method and application of functionalized nano silicon dioxide / resorcinol-formaldehyde microspheres

    CN110756177A

  • Porous wave-absorbing composite material with snake scale-like structure on surface and preparation method of porous wave-absorbing composite material

    CN118042807A

  • Heat-conducting and wave-absorbing difunctional composite material and preparation method thereof

    CN118165523A

  • Preparation method of functional boron nitride modified PVDF (polyvinylidene fluoride)-based nano-composite dielectric film

    JP2023089954A

Cited By

  • Metal surface wave-absorbing and corrosion-preventing integrated coating and preparation method thereof

    CN119823616A